A Systemacic Review of Vanadium and Derivates : Distribution of Coordination Complex and Application - Alam, Muhammad Nur (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2024)
Vanadium is a metal that has unique characteristics both in the form of free elements, ions, and in the form of complex compounds. In common with other minerals, essential and non-essential, vanadium has a wide range of usual dietary intakes, levels of least observed adverse effects, measures of toxicological exposure, and potential therapeutic effects, with concentration ranges that may be disease specific. This review aims to summarize and evaluate the distribution and interactions between vanadium communities in aquatic, soil, and biological chemical systems. In the aquatic environment, vanadium can be distributed directly by marine microorganisms and marine biota, as well as sediments, which at certain concentrations are very toxic, and several studies have even equated the toxicity of vanadium with other heavy metals such as arsenic, lead, mercury and chromium. In soil, vanadium contamination can originate from parent rocks and anthropogenic activities such as mining, the textile industry, the burning of fossil fuels, and the effects of pesticide use. High concentrations of vanadium can interfere with energy metabolism and matter cycles; inhibits the action of enzymes, protein synthesis, ion transport, and other important physiological processes. However, it is unique because vanadium provides an advantage in plant growth process at low levels. On the other hand, the coordination of vanadium with various types of ligands to make complex compounds significantly enhances the significance of vanadium in various applications such as catalysis in polymerization reactions, and therapeutic agents and drug candidates. Ultimately, although vanadium has demonstrated cytotoxicity in testing as a therapeutic agent, several studies have shown promising opportunities for designing effective and safe vanadium derivates-based antiviral or COVID-19 drug candidates in the future.